A Different View for an Old Disease: NEDDylation and Other Ubiquitin-Like Post-Translational Modifications in Chronic Lymphocytic Leukemia - Arenas, Víctor; Castaño, Jose Luis; Domínguez-García, Juan José; Yáñez, Lucrecia; Pipaón, Carlos (Frontiers in Oncology, 2021)
Despite the enormous amount of molecular data obtained over the years, the molecular etiology of chronic lymphocytic leukemia (CLL) is still largely unknown. All that information has enabled the development of new therapeutic approaches that have improved life expectancy of the patients but are still not curative. We must increase our knowledge of the molecular alterations responsible for the characteristics common to all CLL patients. One of such characteristics is the poor correlation between mRNA and protein expression, that suggests a role of post-translational mechanisms in CLL physiopathology. Drugs targeting these processes have indeed demonstrated an effect either alone or in combination with other aimed at specific pathways. A recent article unveiled an increment in ubiquitin-like modifications in CLL, with many protein members of relevant pathways affected. Interestingly, the inhibition of the NEDD8-activating protein NAE reverted a substantial number of those modifications. The present review gets the scarce data published about the role of NEDDylation in CLL together and establishes connections to what is known from other neoplasias, thus providing a new perspective to the underlying mechanisms in CLL.